Cudzołóstwo w praktyce prawa miejskiego Rzeczypospolitej na przykładzie „Księgi czarnej złoczyńców sądu kryminalnego w Wiśniczu” (koniec XVII–XVIII wieku) - Delimata-Proch, Małgorzata (Czasopismo Prawno-Historyczne, 2018)
The aim of this article is to analyze the issue of adultery in the Polish town of Wisnicz. The basis of the study was “Acta Nigra Maleficorum Wisniciae” (1665–1785). This source provided data from 49 cases. Moreover, it constituted the basis for establishing the number of cases pertaining to adultery, determining the number and origin of the defendants, examining the circumstances of the offense as well as examining the court procedure, sentence and the imposed penalties. The paper attempts to answer all these questions and to present ruminations on the norms which regulate this issue as well as to delineate the attitude of the courts in other Polish towns towards adulterers. Among the aforementioned court cases in Wisnicz, four instances were related to the charge of adultery. The perpetrators of this crime have committed adulterium simplex (it is a category of adultery in which only one person is married). Furthermore, in the course of the discussed love affairs, there were two instances in which only the men were married (the women were single) and the women were married (and the men were single) in the remaining two examples. Only one person was convicted of adultery. The remaining defendants were also charged with murder, infanticide or incitement to commit these crimes. The love affairs mentioned above were brief in character. Also two of the people charged with adultery were servants of their respective lovers. Finally, the circumstances of these acts were passion and deserting the wife by her husband. Another aim of the article was to delineate the punishment system. Just one person was convicted of adultery only. It was treated as a felony then and punished by death in the form of decapitation. In this instance, the sentence was subsequently commuted to a fine. Additionally, it should be added that both penalties were prescribed by the urban legal principles for this crime. All perpetrators who were found guilty of adultery were sentenced to death. However, the punishment was commuted in each case to flogging. This commutation correlates with a general view on the liberalization of the punishment system in the 18th century.